Pathological Findings in Chronic Inflammatory Demyelinating Polyradiculoneuropathy: A Single-Center Experience - Luigetti, Marco (Brain Sci, 2020)
Objective: Segmental demyelination is the pathological hallmark of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but other elementary lesions are frequently observed, configuring a series of different pathological pictures. In this article, we review the pathological findings of a large series of sural nerve biopsies from our cohort of CIDP patients. Patients and Methods: Patients with CIDP who underwent nerve biopsy were retrospectively selected from those referred to the Institute of Neurology of the “Università Cattolica del Sacro Cuore” in Rome, Italy, from 1982 to February 2020. Sural nerve biopsy was performed according to standard protocols. Results: Sural nerve biopsy was performed in 43/130 CIDP patients. Demyelinating abnormalities and axonal loss were found in 67.4% and 83.7% of biopsies, respectively. Conversely, onion bulbs and inflammatory infiltrates were rare (18.6% and 4.7%, respectively). In three cases, we observed normal pathological findings. Conclusions: A pathognomonic pathological finding of CIDP cannot be established, but we confirm the utility of nerve biopsy in this setting to confirm the diagnosis (also in atypical phenotypes) and to elucidate pathogenic mechanisms.